How Europe missed the transistor. - Riordan, M. (IEEE spectrum)
This paper relates how the invention of the transistor occurred twice and independently of each other. In late 1948, shortly after Bell Telephone Labs announced the invention of the transistor, surprising reports began coming in from Europe about how two physicists from the German radar program, claimed to have invented a strikingly similar semiconductor device, which they called the transistron. This dual, nearly simultaneous breakthrough can be attributed in part to the tremendous wartime advances in purifying silicon and, in particular, germanium. In both cases, germanium played the crucial gateway role, for in the immediate postwar years it could be refined much more easily and with substantially higher purities than silicon.